Communicating Ideal Social Institution: A Reading of Francis Bacon’s Of Judicature - Singh , Alka (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
Francis Bacon's essay